Mechanical Properties of Typha Angustata/ Vetiver/Banana Fiber Mat Reinforced Vinyl Ester Hybrid Composites. Issue 13 (1st December 2022) - Stalin, A.; Mothilal, S.; Vignesh, V.; Nagarajan, K. J.; Karthick, T.
ABSTRACT: The natural fiber mat is a better replacement for synthetic fiber which is reinforced with polymer composites for advanced engineering application. For the first time, the present experiment was carried out to evaluate the mechanical properties of Typha angustata /Vetiver/Banana fiber/mat reinforced vinyl ester hybrid composites. Eight different types of single and bi-layer hybrid fiber mat composites at 45° and 90° direction were fabricated through compression molding techniques. The Typha angustata double-layer fiber mat composites yield excellent tensile and flexural properties. Tensile tests revealed that the ultimate strength is about 60 MPa, the tensile modulus is 3.56 GPa and elongation break at 1.39%. The flexural strength is estimated to be around 79 MPa, respectively. The Typha angustata /Banana mat composites exhibited better impact strength and hardness due to the hybridization of two natural fibers. The impact strength and hardness of composites are observed to be around 238 kJ/m 2 and 82. The surface morphologies of the fractured composites specimen were characterized by scanning electron microscope analysis.